THE WORLD ECONOMIC CRISIS AND ITS IMPACT ON THE ECONOMIC DEVELOPMENT OF THE CENTRAL ASIAN COUNTRIES - MIGRANIAN, Aza (CENTRAL ASIA AND THE CAUCASUS, 2009)
In the Central Asian (CA) countries, the world crisis has mainly had an impact on the financial and investment sphere. The region does not have enough of its own economic resources to overcome the consequences, so it will have to turn for the most part to influential neighbors. The nature and manifestations of crisis phenomena depend on the level of development and integration of the economic systems of different states into the world economy. Let’s take a look at the situation that has developed in the CA countries under the influence of the world financial crisis, as well as at the possible ways to overcome it and the prospects for the region’s further development. Since the crisis began, there has been a significant drop in the growth rates of the macroeconomic indices in Kazakhstan’s economy. The 2008 year-end results were not encouraging—the financial and economic spheres had obviously experienced a slump. By the end of 2008, however, the powers that be had managed to halt the decline in financial indices. But it was the lower investment activity and difficult financial situation in the banking sector in 2007 that led to the economic crisis. This is confirmed by the data of Kazakhstan’s Statistics Agency.1 The GDP index for 2008 amounted to 103.2% compared to the previous year. Goods production accounted for 45% and services for 52.5%. The total production volume decreased by 2.2% (3,045.9 billion tenge) from January to June 2009 compared to the same period in 2008, giving rise to a corresponding change in the aforementioned indices—36.3% (goods) and 65.8% (services).2 The production branches—oil and mining—suffered the most from the crisis. The drop-in growth rates in these branches corresponds to the downward trends in economies throughout the world. This reduction in production volume led to a change in the sectoral and geographic structures of the country’s industry. The year 2008 was marked by a sharp decrease in Kazakhstan’s oil export revenues. The drop in world oil prices in 2009 prompted a decrease in oil production of 3 million tons, contrary to the government’s official forecast (77 million tons).3 In addition, the Ministry of Economics is expecting a drop in production volume (of approximately 1%) in the metallurgical industry. However, in the first half of 2009, particularly in June, industrial production indices grew (see Figure 1); compared with May 2009, accelerated growth rates were seen in the mining (6.3%) and processing industries (9.9%). Crude oil and metallic ore production and the output of the machine building, metallurgical, and food industries, including beverages and tobacco, increased. The economic crisis in Kazakhstan is having a negative impact on the rise in the price index. By the end of 2008, prices reached an all-time high at every level. For instance, the consumer price index in December 2008 compared to December 2007 amounted to 109.5%. Food prices grew by 10.8%, non-food prices by 5.7%, and the cost of services by 11.4%. The prices for industrial products put out by manufacturing enterprises dropped by 18.6% in December 2008 compared to December 2007.4 The situation improved slightly in the first half of 2009. In June 2009, the consumer price index amounted to 103.9% compared to December 2008. Food prices grew by 3.5%, non-food prices by 4.9%, and the cost of services by 3.3%. In June 2009, industrial product prices increased by 9.7% compared to December 2008.